Butyric acid in functional constipation - Pituch, Aleksandra; Walkowiak, Jarosław; Banaszkiewicz, Aleksandra (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Butyric acid, a short-chain fatty acid, is a major energy source for colonocytes. It occurs in small quantities in some foods, and in the human body, it is produced in the large intestine by intestinalkacteria. This production can be reduced in some cases, for which butyric acid supplementation may be useful. So far, the use of butyric acid in the treatment of gastrointestinal disorders has been limited because of its specific characteristics such as its rancid smell and rapid absorption in the upper gastrointestinal tract. In the Polish market, sodium butyrate has been recently made available, produced by the modern technology of microencapsulation, which allows the active substance to reach the small and large intestines, where butyrate easily dissociates into butyric acid. This article presents the potential beneficial mechanisms of action of butyric acid in defecation disorders, which are primarily associated with reductions in pain during defecation and inflammation in the gut, among others.